Compact Manufacturing Systems Structural Synthesis Automation - Svirsky, Dmitry (Communications - Scientific letters of the University of Zilina, 2000)
In the paper the problems of collective designing of modern industrial systems in the „Lean Production“ concept are considered. The definition of compact manufacturing system (CMS) is given, and the original principles of industrial compactness maintenance have resulted. On the basis of these principles the author offers the technique of designing CMS, formalized up to an integrated algorithm. The result of industrial and operating cycle semiotic modeling was fixed in a basis of the author’s version of simultaneous designing, which is realized at the CAD Centre at Vitebsk state technological university. Both the configuration of the Centre computer network and a model of the design data are discussed. At the end of the paper the examples projected and created CMS are resulted: the compact shop of the machine-building enterprise; the CMS of Reverse Engineering; the CMS of the Rapid Prototyping on the basis of automated laser cutting; the manufacture preparation CMS (Rapid Prototyping & Tooling); the CAD Centre.